2015
DOI: 10.2514/1.j052973
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Sources and Far-Field Noise of Chevron and Round Jets

Abstract: This paper investigates numerically the acoustic sources and far-field noise of chevron and round jets. The acoustic sources are described by the fourth-order space-time velocity cross correlations, which are calculated based on a large-eddy simulation flowfield. Gaussian functions are found to fit the axial, radial, and azimuthal cross correlations reasonably well. The axial length scales are three to four times the radial and azimuthal length scales. For the chevron jet, the cross-correlation scales vary wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…It is obviously shown in Figure 7 of the peak correlation are determined by ∆ + x =ū + τ + , which is in agreement with the convection characteristics observed in Figure 6(c) as well as the spatio-temporal correlations of jet noise sources (e.g. Karabasov et al, 2010Karabasov et al, , 2011Depuru Mohan et al, 2015), local burning area fluctuations (Hemchandra and Lieuwen, 2010), and local chemiluminescence fluctuations (Rajaram and Lieuwen, 2009). The envelope of the peak correlation values indicates the decay of Ω p (∆ + x , τ + ) with the separation distance ∆ + x and/or time delay τ + .…”
Section: ω(∆supporting
confidence: 87%
See 2 more Smart Citations
“…It is obviously shown in Figure 7 of the peak correlation are determined by ∆ + x =ū + τ + , which is in agreement with the convection characteristics observed in Figure 6(c) as well as the spatio-temporal correlations of jet noise sources (e.g. Karabasov et al, 2010Karabasov et al, , 2011Depuru Mohan et al, 2015), local burning area fluctuations (Hemchandra and Lieuwen, 2010), and local chemiluminescence fluctuations (Rajaram and Lieuwen, 2009). The envelope of the peak correlation values indicates the decay of Ω p (∆ + x , τ + ) with the separation distance ∆ + x and/or time delay τ + .…”
Section: ω(∆supporting
confidence: 87%
“…In a series of recent studies on modelling the two-point space-time correlation of jet noise sources (e.g. Karabasov et al, 2010Karabasov et al, , 2011Depuru Mohan et al, 2015), it was observed that this correlation can be well represented by the Gaussian-type function commonly used in classical turbulence. Tam (2015) recently proposed that the spectral shape of combustion noise from hydrocarbon fuels is the same as the similarity spectrum of the large turbulence structure noise from high-speed jets, regardless of the turbulence level or fuel properties.…”
Section: Correlation Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…38,39,40 In our preliminary RANS simulations reported here, we have adopted the standard k − model; 41 it was also found to be the most appropriate for RANS simulations of serrated jets required for noise prediction using the acoustic analogy approach. 9 All simulations reported here were performed using the open-source CFD package OpenFOAM. 42 The rhoSimpleFoam solver was used, which is a steady-state SIMPLE solver for RANS of compressible flows.…”
Section: Rans Simulationsmentioning
confidence: 99%
“…5,6,7 Another approach that is sometimes favored is empirical noise models that invoke an acoustic analogy and take as input an estimate of the scales of turbulence fluctuations in the jet plume, usually using Reynolds-averaged Navier Stokes (RANS) simulations. 8,9 Here, we propose to build the foundation for a third alternative that is explained now.…”
Section: Introductionmentioning
confidence: 99%